Rapid identification of Enterobacteriaceae from blood cultures with the Micro-ID system. - Edberg, S C (1979)
Micro-ID is a new test system designed to identify members of the family Enterobacteriaceae in 4 h. It consists of 15 biochemical tests on reagent-impregnated paper disks; each test is in its own compartment in a molded plastic tray. Based on the pattern of positive and negative biochemical reactions, a five-digit octal code number is calculated. A computer-generated identification manual accompanies the product, and for each octal code listed there is a numerical value that represents the unknown isolate's degree of fit to a typical organism (LFR), a second numerical value that represents its separation from other organisms (PNOR), and a verbal description of the quality of identification. Only one reagent is added to the system. Manufacturer's directions were modified in this laboratory to allow identification from a turbid blood culture bottle within 4 h. Based on 330 routine clinical cultures tested, there was a 96.1% agreement with conventional identification to the genus and species level: 1.2% yielded first two choices possible, with one being the correct choice; 1.2% provided a correct genus, but no species identification; and 1.5% produced an incorrect identification. The Micro-ID is an accurate, facile system for the rapid identification of Enterobacteriaceae from blood cultures.